PENGEMBANGAN MODEL PENYEDIAAN RUMAH UNTUK MEMENUHI PERMINTAAN DI INDONESIA - Albani Musyafa (Structure, 2023)
Procurement of residential buildings or houses in a region requires a standard calculation method. In reality, such planning for housing in Indonesia has not been calculated based on a standard. With such standard, the development stage can be carried out with measurable resource requirements. The purpose of this research is to develop a method for calculating housing needs for an area so that this method can be used as a basis for procurement of housing in regions in Indonesia. The methodology used in this research is drafting the concept, trial and error based on the concept, discussing with experts and validating the results. The result of this research indicated that this calculation method could be used at various levels of the regions in Indonesia.Keywords: planning, procurement, housing, region